Polysorbates degrading enzymes in biotherapeutics – a current status and future perspectives - Felix, Marius Nicolaus; Waerner, Thomas; Lakatos, Daniel; Reisinger, Bernd; Fischer, Simon; Garidel, Patrick (Frontiers in Bioengineering and Biotechnology, 2025)
Polysorbates, in particular polysorbate (PS) 20 and 80, are the most commonly used surfactants for stabilising biotherapeutics produced by biotechnological processes. PSs are derived from ethoxylated sorbitan (a derivative of sorbitol) esterified with fatty acids of varying chain length and degree of saturation. In the past, these surfactants have been reported to have specific liabilities. Chemical (oxidations and hydrolyses) and enzymatic degradations have been reported to affect the stability of PS in drug products. Specifically, the presence of trace amounts (sub-ppm) of certain host cell proteins (HCPs) can induce enzymatic PS degradation, which can lead to the release of free fatty acids during storage over time. Enzymatic polysorbate degradation may impair the functionality of the surfactant in stabilising therapeutic proteins, leading to the formation of visible and/or sub-visible particles in biopharmaceutical drug products. This review summarises the enzymes currently known to be involved in the degradation of polysorbate in mammalian biotechnological processes for therapeutic proteins. In recent years, advanced analytical methods have been developed to qualify and quantify the PS-degrading enzymes. Most of these assays are based on mass spectrometry with a preceding HCP enrichment approach. Efforts were made to measure the enzyme activity and correlate it with observed PS degradation. The impact on drug product quality attributes, including fatty acid solubility and phase separation, up to the formation of visible particles, and the potential induction of protein and protein/fatty acid mixed particles as well as the sensitivity of specific PS quality towards enzymatic degradation, was considered. Various drug substance (DS) mitigation strategies related to the occurrence of PS degrading enzymes are discussed as amongst them the generation of stable HCP knockout cell lines, which are also carefully analysed. The underlying opinion article reflects the undergoing discussions related to PS degrading enzymes and focusses on (i) impact on drug product, (ii) analytics for identification/quantification (characterisation) of the PS degrading enzymes, (iii) enzyme activity (iv) currently identified enzymes, and (v) potential mitigation strategies to avoid enzymatic PS degradation during DS manufacturing.